Krüppel-like factor 4 modulates the miR-101/COL10A1 axis to inhibit renal fibrosis after AKI by regulating epithelial–mesenchymal transition - Jingying Zhao; Xiuli Wang; Yubin Wu; Chengguang Zhao (Renal Failure)
Acute kidney injury (AKI) can progress to renal fibrosis and chronic kidney disease (CKD), which reduces quality of life and increases the economic burden on patients. However, the molecular mechanisms underlying renal fibrosis following AKI remain unclear. This study tested the hypothesis that the Krüppel-like factor 4 (KLF4)/miR-101/Collagen alpha-1X (COL10A1) axis could inhibit epithelial-mesenchymal transition (EMT) and renal fibrosis after AKI in a mouse model of ischemia-reperfusion (I/R)-induced renal fibrosis and HK-2 cells by gene silencing, overexpression, immunofluorescence, immunohistochemistry, real-time quantitative PCR, Western blotting, dual-luciferase reporter assay, fluorescence in situ hybridization (FISH) and ELISA. Compared with the Sham group, I/R induced renal tubular and glomerular injury and fibrosis, and increased the levels of BUN, serum Scr and neutrophil gelatinase-associated lipocalin (NGAL), Col10a1 and Vimentin expression, but decreased E-cadherin expression in the kidney tissues of mice at 42 days post-I/R. Similarly, hypoxia promoted fibroblastic morphological changes in HK-2 cells and enhanced NGAL, COL10A1, Vimentin, and α-SMA expression, but reduced E-cadherin expression in HK-2 cells. These pathological changes were significantly mitigated in COL10A1-silenced renal tissues and HK-2 cells. KLF4 induces miR-101 transcription. More importantly, hypoxia upregulated Vimentin and COL10A1 expression, but decreased miR-101, KLF4, and E-cadherin expression in HK-2 cells. These hypoxic effects were significantly mitigated or abrogated by KLF4 over-expression in the HK-2 cells. Our data indicate that KLF4 up-regulates miR-101 expression, leading to the downregulation of COL10A1 expression, inhibition of EMT and renal fibrosis during the pathogenic process of I/R-related renal fibrosis.